Die behandeling van VIGS - Geneesmiddels en vaksiene - Wat hou die toekoms in? - Schyf, C. J. van der (Koers, 1990)
The developing epidemic of acquired immunodeficiency syndrome (AIDS) has prompted a broadly based research effort to find drugs and vaccines for preventing and treating this disease. Compounds such as zidovudine (AZT), ampligen and the broad spectrum of pyrimidine dideaxynucleosides have yielded some promise for the treatment of AIDS in terms of better quality of life for sufferers, but no cure is in sight yet. Also the quest for therapeutic and preventative vaccines has also been ongoing for several years. The latest development of the Salk vaccine has led to wild speculation in the lay press of a cure for AIDS. However, some seemingly insurmountable practical and moral-ethical problems beset both the development of AIDS chemotherapy and an AIDS vaccine. The most vexing of these problems is the lack of a suitable animal model for testing and the consequent questions of whether uninfected or HIV-infected but symptom-free volunteers can or should be used in testing potentially lethal compounds or vaccines.